PEMANFAATAN LIMBAH PERTANIAN MENJADI SUMBER ENERGI PADA KELOMPOK TANI BUKIK GOMPONG KABUPATEN SOLOK - Tivany Edwin; Fadjar Goembira; Nuzulia Irawati; Tevina Edwin; Syawal Andika Putra; Ahlul Zikri (LPPM Universitas Andalas, 2024)
Agricultural waste has the potential to be utilized as an environmentally friendly energy source. One such agricultural waste comes from the Bukik Gompong Organic Garden farmer group, which has not been optimally utilized. The aim of this activity is to introduce the importance of processing agricultural waste into an energy source and provide assistance in making biomass stoves to the farmer group. It is hoped that this activity will help reduce the production waste from Bukik Gompong Organic Garden, thus mitigating environmental damage. This activity was carried out in Bukik Gompong, Solok Regency, West Sumatra Province. The target audience is the Bukik Gompong farmer group. The implementation method includes providing guidance on the utilization of agricultural waste as an energy source and assisting in the production and application of biomass stoves. Agricultural waste can be utilized as an alternative energy source if processed properly. This community service activity was conducted with the Bukik Gompong Organic Garden farmer group as an effort to reduce agricultural waste. The results of this activity indicate that the farmer group understands the benefits of processing agricultural waste into an energy source such as biochar. The farmer group also gains knowledge in making biomass stoves. The results of this activity can be followed up by the farmer group using eucalyptus, tea, corn, and coffee waste, which have the potential to become environmentally friendly fuels, especially if dried beforehand. In conclusion, this activity is highly beneficial for the farmer group in processing agricultural waste into an energy source.